Assessing Exclusionary Conduct in Abuse of Dominance: the relevance of the Extraterritoriality Rule and Public Interest for Developing Countries - Adeleke, Olufolahan (Department of Commercial Law, 2014)
Competition Law is governed by empowering legislation. Legislation in most developing and third world economies are mostly fashioned after the existing framework of legislation originating from the European Union (EU) or the United States of America (USA). While a lot of these pieces of legislation are often modified to suit the needs of these developing countries, it is usually not the case that a cautious approach is taken to ensure that imported legislation is designed to meet the specific national challenges of such a country. The Courts in most jurisdictions especially in the USA and the EU have attempted to deal with the lapse in competition legislations by giving landmark decisions on significant issues like dominant firms and their unilateral exclusionary behaviors. The big question to consider in this dissertation is how competition laws should apply to dominant firms. This question has raised much interest in recent years. Aside from establishing which firms have substantial market power that can harm competition, there have been difficulties in distinguishing competition on the merits from mere anticompetitive conduct. This is more obvious in the case of unilateral exclusionary behaviors and will be the central focus in this dissertation.